Results of an Interdisciplinary Day Care Approach for Chronic Tinnitus Treatment: A Prospective Study Introducing the Jena Interdisciplinary Treatment for Tinnitus - Ivansic, Daniela; Dobel, Christian; Volk, Gerd F.; Reinhardt, Daniel; Müller, Boris; Smolenski, Ulrich C.; Guntinas-Lichius, Orlando (Frontiers in Aging Neuroscience, 2017)
Objective Considering the heterogeneity of the symptoms shown by patients suffering from chronic tinnitus, there are surprisingly few interdisciplinary treatments available, and mostly available only for inpatients. In order to provide an interdisciplinary treatment, we developed a day care concept in which each patient was treated by an ENT doctor, a cognitive behavioral therapist, a specialist for medical rehabilitation and an audiologist (Jena Interdisciplinary Treatment for Tinnitus, JITT). The aim of this study was to observe the changes of tinnitus related distress due to interdisciplinary day care treatment and to determine which factors mediate this change. Subjects and methods Tinnitus annoyance was measured using the Tinnitus Questionnaire on 308 patients with chronic tinnitus. They were treated in the day care unit over five consecutive days between July 2013 and December 2014. Data were collected before treatment when screened (T0), at the beginning (T1) and at the end of the five day treatment (T2), as well as 20 days (T3) and 6 months after treatment (T4). Results Overall, tinnitus annoyance improved significantly from the screening day to the beginning of treatment, and to a much larger degree from the beginning to the end of treatment. The treatment outcome remained stable 6 months after treatment. Patients with the following symptoms displayed higher tinnitus annoyance at T0: dizziness at tinnitus onset, tinnitus sound could not be masked with background noise, tinnitus worsening during physical stress, comorbid psychiatric diagnosis, higher age and higher hearing loss. Loudness of tinnitus perceived in the right ear correlated with tinnitus annoyance significantly. Demographic, tinnitus and strain variables could only explain 12.8% of the variance of the change in tinnitus annoyance from T0 to T4. Out of 39 predictors, the only significant ones were ‘sick leave 6 months before treatment’ and ‘tinnitus annoyance at T0’. Conclusion The newly developed JITT represents a valuable treatment for chronic tinnitus patients with improvement remaining stable for at least 6 months after treatment. Using a large number of variables did not allow predicting treatment outcome which underlines the heterogeneity of tinnitus.